Not sure if I'm right but I think it's 3(x - 6) (x^2 + 5x)
Step-by-step explanation:
3x^3 - 3x^2 - 90x
Apply GCF: 3 (x^3 - x^2 - 30)
Split 30 into -6 and 5
(x^3 - 6x^2) (5x^2 - 30x)
GCF of both: x^2 (x - 6) and 5x (x - 6)
DON'T FORGET TO CARRY THE 3
And your answer is 3 (x - 6) (x^2 + 5x)
Answer:
m= ![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
Step-by-step explanation:
1. Use the slope equation to solve the problem
![\frac{y_{2} -y_{1}}{x_{2} -x_{1} }](https://tex.z-dn.net/?f=%5Cfrac%7By_%7B2%7D%20-y_%7B1%7D%7D%7Bx_%7B2%7D%20-x_%7B1%7D%20%7D)
2. Plug in your values into the equation.
![\frac{4-(-2)}{9-(-7)}](https://tex.z-dn.net/?f=%5Cfrac%7B4-%28-2%29%7D%7B9-%28-7%29%7D)
3. Simplify the equation.
m= ![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
178 * 18 + (98-2)
3204 + 96
3300
(3x5)X2=5x(2x3)
15x2=5x6
30=30